Zinc Acetate Dihydrate Tablet-Associated Gastritis Occurring in a Post-Hematopoietic Stem Cell Transplant Recipient - Masaya Iwamuro; Takehiro Tanaka; Akifumi Matsumura; Seiji Kawano; Yoshiro Kawahara; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
A 65-year-old Japanese woman underwent umbilical cord blood transplantation for acute myeloid leukemia. Zinc acetate dihydrate tablets were administered for hypozincemia after transplantation, and vomiting and appetite loss occurred soon thereafter. Esophagogastroduodenoscopy revealed mucosal redness, erosion, white coat adhesion, and ulcers. Although graft-versus-host disease, intestinal transplant-associated microangiopathy, and cytomegalovirus infection were considered as possible causes, we diagnosed the patient with zinc acetate dihydrate tablet-associated gastric mucosal alterations based on the endoscopic features. This case reinforces the notion that medication-associated gastric lesions should be suspected in patients taking zinc acetate dihydrate tablets.